2018
DOI: 10.1016/j.toxlet.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoke and nicotine suppress expression of activating signaling molecules in human dendritic cells

Abstract: Cigarette smoke has significant toxic effects on the immune system, and increases the risk of developing autoimmune diseases; one immunosuppressive effect of cigarette smoke is that it inhibits the T cell-stimulating, immunogenic properties of myeloid dendritic cells (DCs). As the functions of DCs are regulated by intra-cellular signaling pathways, we investigated the effects of cigarette smoke extract (CSE) and nicotine on multiple signaling molecules and other regulatory proteins in human DCs to elucidate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 63 publications
6
14
1
Order By: Relevance
“…This resulted in 1% ECVE containing approximately 12 μg/ml nicotine and 3% ECVE containing 36 μg/ml nicotine. This is similar to the nicotine concentrations in 0.5-3% cigarette smoke extract (CSE) used in previous studies (Alkhattabi et al 2018).…”
Section: Ecve Preparationsupporting
confidence: 89%
See 3 more Smart Citations
“…This resulted in 1% ECVE containing approximately 12 μg/ml nicotine and 3% ECVE containing 36 μg/ml nicotine. This is similar to the nicotine concentrations in 0.5-3% cigarette smoke extract (CSE) used in previous studies (Alkhattabi et al 2018).…”
Section: Ecve Preparationsupporting
confidence: 89%
“…RPPA was performed as described previously (Alkhattabi et al 2018;Negm et al 2014). We had previously confirmed that the detection of signalling molecules by RPPA gave results consistent with those obtained by western blotting (Negm et al 2014).…”
Section: Reverse-phase Protein Microarray (Rppa)mentioning
confidence: 65%
See 2 more Smart Citations
“…MAM, Poly I:C, LBN) have not yet been assessed. However, considering interactions between the immune system and nicotine [172,173], this is an interesting area of future research.…”
Section: Nicotinementioning
confidence: 99%